2021
DOI: 10.1007/s41748-021-00218-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factor of COVID-19 and Impacts of Meteorological and Social Variables on Its Propagation in Punjab, Pakistan

Abstract: The current study identifies the spatial distribution of COVID-19 cases and its association with meteorological and social variables in Punjab (densely populated province of Pakistan). To identify the COVID-19 propagation, the weekly growth, recovery, and deaths rate have also been calculated. The geographic information system (GIS) has used to determine COVID-19 impacts on gender (male/female), age groups, and causalities over an affected population (km −2 ) for the period of 11th March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Researchers grouped the patients having confirmed COVID-19 cases. About 75% of cases were above 50 years of age (Saddique et al, 2021). Our study aligned with the previous reports and about 73.4 % of patients were older than 50 years of age.…”
Section: D-dimer <200supporting
confidence: 92%
“…Researchers grouped the patients having confirmed COVID-19 cases. About 75% of cases were above 50 years of age (Saddique et al, 2021). Our study aligned with the previous reports and about 73.4 % of patients were older than 50 years of age.…”
Section: D-dimer <200supporting
confidence: 92%
“…Additionally, we noted that individuals between 19 and 39 years were more susceptible to infection. Previous reports have shown that a significant proportion of young adults were affected in most districts of Punjab [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karachi is the only major port city on the Arabian Sea with approximately 30% of the nation's industrial sector which contributes more than 20% to the national GDP of Pakistan (Fazal and Hotez, 2020). However there are several other dense cities in Pakistan like Lahore and Faisalabad -that belong to Punjab which is a densely populated province and contributes 110 million people to the total population of Pakistan (Saddique et al, 2021).…”
Section: Population Densitymentioning
confidence: 99%